2022
DOI: 10.1039/d1ma01155c
|View full text |Cite
|
Sign up to set email alerts
|

Poly(lactic-co-glycolic acid) encapsulated platinum nanoparticles for cancer treatment

Abstract: Metal nanoparticles have been of interest to the field of nanomedicine due to their potential for cancer treatment, diagnosis, and antimicrobial activity. Particularly, platinum nanoparticles (PtNPs) have been reported to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 66 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…Encouraged by the results and previous experience, we further tested whether the partial platinum coating would influence cell viability and microrobot uptake in cells . Furthermore, based on previously published studies, it was expected that fueled microrobots would be more likely to target, enter, and accumulate within the cells in comparison to static microparticles. , Prior to these studies, possible limitations were considered.…”
Section: Resultsmentioning
confidence: 99%
“…Encouraged by the results and previous experience, we further tested whether the partial platinum coating would influence cell viability and microrobot uptake in cells . Furthermore, based on previously published studies, it was expected that fueled microrobots would be more likely to target, enter, and accumulate within the cells in comparison to static microparticles. , Prior to these studies, possible limitations were considered.…”
Section: Resultsmentioning
confidence: 99%
“…Again, biofabricated platinum NPs are biocompatible and have catalytic and anticancer activity [ 167 , 300 ]. In another study, researchers found that poly(lactic- co -glycolic acid) and polyethylene glycol-modified platinum NPs loaded with anti-EGFR showed better efficacy in triple-negative breast cancer [ 302 ]. Furthermore, porous Au–Pt NPs loaded with doxorubicin modified with c-RGD exhibit better drug release patterns and enhanced anticancer properties via photo-induced and photothermal processes.…”
Section: Novel Nanocarriers Based Treatment Approachmentioning
confidence: 99%
“…Metal nanoparticles (NPs) have been extensively studied due to their distinct and diverse electronic, optical, catalytic, and magnetic properties as compared to their bulk counterparts, which has led to a broad range of applications. , For example, platinum (Pt) NPs have attracted considerable attention in areas of electrocatalysis in fuel cells, , sensing, cancer treatment, chemical recycling of plastics, and catalysis for the chemical vapor deposition growth of semiconductor nanowires . The properties and activity of functional metal NPs depend strongly on their size and shape. , The effect of NP size and shape on the localized surface plasmon resonance (LSPR) of noble metal NPs such as Au , and Ag , is well documented.…”
Section: Introductionmentioning
confidence: 99%